2023
DOI: 10.3390/jcm12134426
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Connectivity of Critical Deep Brain Structures and Their Potential Clinical Application in Brain Stimulation

Qiao Kong,
Valeria Sacca,
Meixuan Zhu
et al.

Abstract: Subcortical structures, such as the hippocampus, amygdala, and nucleus accumbens (NAcc), play crucial roles in human cognitive, memory, and emotional processing, chronic pain pathophysiology, and are implicated in various psychiatric and neurological diseases. Interventions modulating the activities of these deep brain structures hold promise for improving clinical outcomes. Recently, non-invasive brain stimulation (NIBS) has been applied to modulate brain activity and has demonstrated its potential for treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 120 publications
(138 reference statements)
0
2
0
Order By: Relevance
“… 72 These regions are involved in multiple functions including memory, reward, learning, and emotional response, and dysregulated function is implicated in several psychiatric and neurological diseases. 73 In addition to reporting the efficacy of a novel polysaccharide-based coating, this current study also illuminates the extracellular neurophysiological activity of striatal medium spiny neurons, which play a critical role in driving motivated behavior. Future work will explore the coating's effect on the tissue response and neurophysiological recording quality for a chronic implantation period.…”
Section: Discussionmentioning
confidence: 92%
“… 72 These regions are involved in multiple functions including memory, reward, learning, and emotional response, and dysregulated function is implicated in several psychiatric and neurological diseases. 73 In addition to reporting the efficacy of a novel polysaccharide-based coating, this current study also illuminates the extracellular neurophysiological activity of striatal medium spiny neurons, which play a critical role in driving motivated behavior. Future work will explore the coating's effect on the tissue response and neurophysiological recording quality for a chronic implantation period.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, we observed functional and anatomical connections between the mPFC and hippocampus, amygdala, and nucleus accumbens, while the precuneus exhibited connections with the hippocampus and amygdala. These findings designate the mPFC and precuneus as promising targets for NIBS to modulate deep brain structures implicated in psychiatric and neurological disorders, as well as chronic pain [ 161 ]. Prior research has demonstrated that hub nodes in the brain tend to have high average controllability within the DMN, indicating that the modulation of hub regions may have significant impacts on brain system functioning [ 162 ].…”
Section: Discussionmentioning
confidence: 99%